Serum levels of ACE2 are higher in patients with obesity and diabetes - Valur Emilsson; Elias F. Gudmundsson; Thor Aspelund; Brynjolfur G. Jonsson; Alexander Gudjonsson; Lenore J. Launer; John R. Lamb; Valborg Gudmundsdottir; Lori L. Jennings; Vilmundur Gudnason (Wiley, 2021)
Abstract Objective As severity of outcome in COVID‐19 is disproportionately higher among individuals with obesity, smokers, patients with hypertension, kidney disease, chronic pulmonary disease, coronary heart disease (CHD), and/or type 2 diabetes (T2D), serum levels of ACE2, the cellular entry point for the coronavirus SARS‐CoV‐2, were examined in these high‐risk groups. Methods Associations of ACE2 levels to smokers and patients with hypertension, T2D, obesity, CHD, or COPD were investigated in a single center population‐based study of 5457 Icelanders from the Age, Gene/Environment Susceptibility Reykjavík Study (AGES‐RS) of the elderly (mean age 75 ± 6 years), using multiple linear regression analysis. Results Serum levels of ACE2 were higher in smokers and individuals with T2D and/or obesity while they were unaffected in the other patient groups. Conclusion ACE2 levels are higher in some patient groups with comorbidities linked to COVID‐19 including obesity and T2D and as such may have an emerging role as a circulating biomarker for severity of outcome in the disease.